Valentin Vodnik’s activities for the linguistic awareness of Slovenians at the turn of the 18th and 19th centuries - Gruda, Marlena (Poznańskie Studia Slawistyczne, 2024)
The text presents the figure of the first Slovenian poet, educator, scholar, publicist, politician, clergyman and mountaineer, Valentin Vodnik (1758–1819), one of the representatives of the Slovenian Enlightenment and National Revival, author of the first grammar written in Slovenian, many text-books, guides and poems. Based on the analysis of historical data dealing with Vodnik and his scientific and didactic texts (Pismenost, Abezeda), journalism (Povedanje od slovenskiga jezika) and poetic texts (Dramilo, Ilirija oživljena, Moj spomenik, Zadovoljni Kranjc, Vršac), Vodnik’s significant contribution to the development of education, the improvement of the level of education among Slovenians, the state of linguistic awareness and the sense of national identity of Slovenians is noted.